Lifestyle Interventions: Reasons for Therapeutic Outcome - Baydala, Angelina M.; Hiebert, Bryan; Malec, Carol A. (Canadian Journal of Counselling and Psychotherapy, 2007)
Self-efficacy is proposed as a mediating factor underlying positive outcome as observed in lifestyle and exercise programs. Studies are reviewed which indicate that lifestyle education and exercise programs improve quality of life, health, and wellness. However, improved physiological fitness is equivocally related to ability to cope with stressors and psychological well being. The mixed results seem to indicate that something other than physical fitness is significantly contributing to the improved psychosocial functioning observed subsequent to lifestyle counselling and exercise training. It is postulated in accordance with social learning theory that cognitive factors such as improved self-confidence and self-efficacy may be mediating the effect of fitness on stress.